Hyperphosphatemia is associated with patency loss of arteriovenous fistula after 1 year of hemodialysis - Ju-Young Moon; Hyae Min Lee; Sang-Ho Lee; Tae-Won Lee; Chun-Gyoo Ihm; Young-Il Jo; Sang-Woong Han; Sug-Gyun Shin (The Korean Society of Nephrology, 2015)
Background: The patency of arteriovenous access is important for stable and effective hemodialysis, and long-term technical survival is best achieved with a native arteriovenous fistula (AVF). However, maintaining AVF patency remains a challenge. This study was designed to determine the independent prognostic factors for AVF patency according to hemodialysis duration. Methods: The primary study end point was unassisted patency of the AVF, which was defined as the time from the first fistula surgery to the first AVF failure. AVF failure was defined as an event that required percutaneous intervention or surgery to revise or replace the fistula, which occurred at least 2 months after fistula formation. Results: We enrolled 478 patients with a mean age of 55.5±14.0 years, and mean duration of dialysis was 2.5±2.1 years. There were 109 cases (22.8%) of AVF failure. The factors related to AVF patency differed according to hemodialysis duration. Using a Cox-adjusted model, we observed a significant correlation between the incidence of AVF failure and diabetes within the initial 12 months of hemodialysis. Uncontrolled hyperphosphatemia (mean serum phosphorus>5.5 mg/dL during hemodialysis) was associated with patency loss of AVF after 1 year of hemodialysis. Conclusion: Various factors were associated with the development of patency loss of AVF as hemodialysis duration differed, and a preventive role of hyperphosphatemia control in AVF survival needs further clinical study.